2016
DOI: 10.1038/srep37548
|View full text |Cite|
|
Sign up to set email alerts
|

Narrowing the spread in CMIP5 model projections of air-sea CO2 fluxes

Abstract: Large spread appears in the projection of air-sea CO2 fluxes using the latest simulations from the Coupled Model Intercomparison Project Phase 5 (CMIP5). Here, two methods are applied to narrow this spread in 13 CMIP5 models. One method involves model selection based on the ability of models to reproduce the observed air-sea CO2 fluxes from 1980 to 2005. The other method involves constrained estimation based on the strong relationship between the historical and future air-sea CO2 fluxes. The estimated spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 60 publications
7
24
0
Order By: Relevance
“…Thus, the contribution of internal variability to the ocean carbon uptake uncertainty, and the future evolution of this internal variability remain poorly quantified. Moreover, as of now, CMIP5 historical simulations are not expected to reproduce the decreasing decadal trends in the ocean carbon uptake during 1992–2001 (Wang et al, ) as found in observational estimates. Hindcast models forced with atmospheric reanalysis may better capture decadal variations of the ocean carbon uptake driven by climate variability.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Thus, the contribution of internal variability to the ocean carbon uptake uncertainty, and the future evolution of this internal variability remain poorly quantified. Moreover, as of now, CMIP5 historical simulations are not expected to reproduce the decreasing decadal trends in the ocean carbon uptake during 1992–2001 (Wang et al, ) as found in observational estimates. Hindcast models forced with atmospheric reanalysis may better capture decadal variations of the ocean carbon uptake driven by climate variability.…”
Section: Introductionsupporting
confidence: 55%
“…Thus, the contribution of internal variability to the ocean carbon uptake uncertainty, and the future evolution of this internal variability remain poorly quantified. Moreover, as of now, CMIP5 historical simulations are not expected to reproduce the decreasing decadal trends in the ocean carbon uptake during 1992-2001 (Wang et al, 2016) ESM-based perturbed initial conditions ensembles allow for a consistent evaluation of both forced signals and internal variability within the same model. The important role of internal climate variability for projections of ocean biogeochemistry has been already confirmed, using such ensembles (containing 30 members) McKinley et al, 2016;Rodgers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCP-M simulations commence in 1751 and therefore incorporate an extra 100 years of fossil fuel and land use change emissions beyond the CMIP5 model results presented in Jones et al (2013). Wang et al (2016) quote a range of 412-649 PgC Figure 5. SCP-M modelling results compared with modern atmospheric and ocean GLODAPv2 data for (a) atmospheric CO 2 and δ 13 C, (b) atmospheric 14 C, (c) ocean δ 13 C, (d) 14 C, (e) DIC, and (f) the carbonate ion proxy.…”
Section: Modern Carbon Cycle Simulationmentioning
confidence: 99%
“…Broecker, 1982;Sarmiento and Toggweiler, 1984;Kohfeld and Ridgewell, 2009;Sigman et al, 2010), alongside changes in the terrestrial biosphere stock of carbon (Francois et al, 1999;Ciais et al, 2012;Peterson et al, 2014;Hoogakker et al, 2016). Active theories within the ocean realm include changes in ocean biology (Martin, 1990;Watson et al, 2000;Martinez-Garcia et al, 2014), ocean circulation and mixing (Sarmiento and Togg- Figure 7. Panel (a) shows the annual uptake of CO 2 by the ocean in each of the RCPs over the period 1751-2100, modelled with SCP-M. By 2100, SCP-M estimates a range of 0-6 PgC yr −1 across the RCPs as estimated by CMIP5 models, reproduced from Jones et al (2013).…”
Section: Introductionmentioning
confidence: 99%